A Cannabinoid 2-Selective Agonist Inhibits Allogeneic Skin Graft Rejection In Vivo - Jayarajan, Senthil; Meissler, Joseph J.; Adler, Martin W.; Eisenstein, Toby K. (Frontiers in Pharmacology, 2022)
Previous work from our laboratory showed that a CB2 selective agonist, O-1966, blocked the proliferative response of C57BL/6 mouse spleen cells exposed to spleen cells of C3HeB/FeJ mice in vitro in the Mixed Lymphocyte Reaction (MLR). The MLR is widely accepted as an in vitro correlate of in vivo grant rejection. Mechanisms of the immunosuppression induced by the cannabinoid were explored, and it was shown that O-1966 in this in vitro assay induced CD25+Foxp3+ Treg cells and IL-10, as well as down-regulated mRNA for CD40 and the nuclear form of the transcription factors NF-κB and NFAT in T-cells. The current studies tested the efficacy of O-1966 in prolonging skin grafts in vivo. Full thickness flank skin patches (1-cm2) from C3HeB/FeJ mice were grafted by suturing onto the back of C57BL/6 mice. O-1966 or vehicle was injected intraperitoneally into treated or control groups of animals beginning 1 hour pre-op, and then every other day until 14 days post-op. Graft survival was scored based on necrosis and rejection. Treatment with 5 mg/kg of O-1966 prolonged mean graft survival time from 9 to 11 days. Spleens harvested from O-1966 treated mice were significantly smaller than those of vehicle control animals based on weight. Flow cytometry analysis of CD4+ spleen cells showed that O-1966 treated animals had almost a 3-fold increase in CD25+Foxp3+ Treg cells compared to controls. When dissociated spleen cells were placed in culture ex vivo and stimulated with C3HeB/FeJ cells in an MLR, the cells from the O-1966 treated mice were significantly suppressed in their proliferative response to the allogeneic cells. These results support CB2 selective agonists as a new class of compounds to prolong graft survival in transplant patients.